2022
DOI: 10.1111/gwao.12810
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing liminality: At the crossroads of neoliberal and gendered experiences

Abstract: Women entrepreneurship literature has unveiled the gendered assumptions of entrepreneurship. More recently, critical woman entrepreneurship literature is increasingly focusing on the neoliberal discourses in women entrepreneurship. What remains relatively under‐explored is how women entrepreneurs experience the tensions amidst neoliberal and gendered experiences especially in the context of the Global South. Based on the narratives of middle to upper‐middle‐class women entrepreneurs in India, I find that being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…Studies have found that gender roles and segregation in societies play a significant role in influencing women's career choices (Shetty et al, 2022). A recent study in India found that though becoming an entrepreneur gave middle to uppermiddle-class women neoliberal agency, their career choices were constrained by deep-seated gender norms (Doshi, 2022).…”
Section: Entrepreneurship As a Career For Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that gender roles and segregation in societies play a significant role in influencing women's career choices (Shetty et al, 2022). A recent study in India found that though becoming an entrepreneur gave middle to uppermiddle-class women neoliberal agency, their career choices were constrained by deep-seated gender norms (Doshi, 2022).…”
Section: Entrepreneurship As a Career For Womenmentioning
confidence: 99%
“…, 2022). A recent study in India found that though becoming an entrepreneur gave middle to upper-middle-class women neoliberal agency, their career choices were constrained by deep-seated gender norms (Doshi, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%